Synthesis of Novel Coumarin Derivatives 7,8-Fused onto Thiazole - Frere, Stephane; Thiery, Valerie; Besson, Thierry (Letters in Organic Chemistry, 2005)
The synthesis of some novel thiazolocoumarins is described. These polyheterocyclic compounds have been synthesized under microwave irradiation via the corresponding imino-1,2,3-dithiazoles besides cyanoimidoyl chloride derivatives.
Keywords: Coumarin